How Do Endodontic Irrigation Solutions Affect the Surface Roughness of Bulk Fill Resin Composite? - Topbaş, Celalettin; Öztekin, Faruk (Ataturk Universitesi, 2024)
Objective: The goal is to find out how irrigation and chelating solutions change the average surface roughness (Ra) of resin composites when root canal treatment is done on teeth with composite restorations. Methods: A total of 40 disc-shaped composite specimens (Tetric®-N-Ceram-Bulk-Fill-IVA) were used in the study. The specimens were randomly divided into 4 groups (n=10) and Ra values were measured before treatment. Group1 (Gr1) was then immersed in 5% sodium hypochlorite (NaOCl), group2 (Gr2) in 17% ethylenediaminetetraacetic acid (EDTA), group3 (Gr3): 10% citric acid (CA), group4 (Gr4): 0.9% saline (SS) for 15 minutes. After treatment, the Ra values of the samples were measured again. Comparison of Ra values before and after treatment was performed by paired samples t-test, and one-way ANOVA analysis was used for comparison between groups. Results: There was a statistically-significant difference between the 4 groups in terms of post-treatment Ra measurements (p<0.05). While there was no statistically-significant difference between the pre-treatment and post-treatment Ra values in NaOCl and SS (p>0.05). There is a statistically-significant difference between the pre-treatment and post-treatment Ra values in EDTA and CA (p<0.05). There is also a statistically-significant difference between NaOCl and SS and EDTA and CA in terms of post-treatment Ra values (p<0.05). Conclusion: Among the solutions used in our study, EDTA and CA increased the Ra values on resin composites. It is recommended to polish the surface of composite restorations after the treatment to avoid problems related to the increase in roughness after the irrigation procedure. © 2024, Ataturk Universitesi. All rights reserved.
Endodontik İrrigasyon Solüsyonları Bulk Fill Reçine Kompozitin Yüzey Pürüzlülüğünü Nasıl Etkiler?
Keywords: bulk fill; composite resin; Endodontic irrigation; surface roughness